Drug-induced dementia: a real-world pharmacovigilance study using the FDA Adverse Event Reporting System database - Lisi Xu; Ruonan Zhang; Xiaolin Zhang; Xiuli Shang; Daifa Huang (Therapeutic Advances in Neurological Disorders)
Background: Dementia is a serious adverse event (AE) that requires attention in clinical practice. However, information on drug-induced dementia is limited. The U.S. FDA Adverse Event Reporting System (FAERS) serves as an important resource for identifying real-world adverse drug reactions and safety signals. Objective: This study aimed to use FAERS data to identify drugs associated with increased dementia risk. Design: A secondary analysis of the FAERS database was conducted using disproportionality analysis methods. Methods: We reviewed dementia-related reports in the FAERS database from the first quarter of 2004 to the fourth quarter of 2023, used the Medical Dictionary for Regulatory Activity to identify dementia cases and summarized the corresponding list of potential medications, counted the dementia-causing medication classes with the highest frequency of reports, and disaggregated all medications. Results: The study identified 31,881 dementia-related AEs in the FAERS database, with an increasing trend over time, particularly among females and individuals over 65. Apixaban had the most reports (1631). Disproportionality analyses revealed that rivastigmine, nicergoline, aducanumab, amlodipine/atorvastatin, and dihydroergometrine had the highest risk, based on reporting odds ratio, proportional reporting ratio, and information component. Only valproate and tramadol among the top 50 drugs included a potential dementia risk in their package inserts. Conclusion: This study identified a list of medications associated with dementia risk, many of which lack dementia warnings on their labels. Increased monitoring is necessary for high-risk individuals, and further research is required to clarify these associations and improve patient safety.